Mapping the Human Leukocyte Antigen Diversity among Croatian Regions: Implication in Transplantation - Zorana Grubic; Marija Maskalan; Katarina Stingl Jankovic; Marija Burek Kamenaric; Renata Zunec (Journal of Immunology Research)
In the present study, HLA allele and haplotype frequencies were studied using the HLA data of 9277 Croatian unrelated individuals, typed using high-resolution methods for the HLA-A, -B, -C, and -DRB1 loci. The total numbers of observed alleles were 47 for HLA-A, 88 for HLA-B, 34 for HLA-C, and 53 for HLA-DRB1. HLA-A∗02:01 (29.5%), B∗51:01 (10.5%), C∗04:01 (15.8%), and DRB1∗16:01 (10.4%) were the most frequent alleles in the Croatian general population. The three most frequent haplotypes were HLA-A∗01:01~C∗07:01~B∗08:01~DRB1∗03:01 (4.7%), HLA-A∗03:01~C∗07:02~B∗07:02~DRB1∗15:01 (1.7%), and HLA-A∗02:01~C∗07:01~B∗18:01~DRB1∗11:04 (1.5%). Allele and haplotype frequencies were compared between national and regional data, and differences were observed, particularly in the North Croatia region. The data has potential use in refining donor recruitment strategies for national registries of volunteer hematopoietic stem cell donors, solid organ allocation schemes, and the design of future disease and anthropological studies.